Relationship beliefs and compatibility preferences in romantic partners - Marchi, Alessia; Jonason, Peter K. (Studia Psychologica: Theoria et praxis, 2023)
Recently, we identified 24 factors (e.g., appearance, conformity, leisure) that may capture whether people want to be similar or different from their sexual and romantic partners on different qualities in 274 (nWomen = 225) Italians (Marchi et al., 2023; Personality and Individual Differences). In this brief report, we reanalyzed that data, but now turn our attention to content we did not report previously about relationship beliefs. Participants believed similarity was more important than complementary in relationships but beliefs that physical attractiveness is important may trump them both. However, belief that physical attractiveness is important was unrelated to any of the compatibility factors and complementarity beliefs were only related to three of them, while nearly two-thirds of the correlations with similarity beliefs were significant (e.g., residence, speech, intellect). We discussed our results in terms of how different generalized relationship beliefs may manifest themselves in how similar or different people want their romantic and sexual partners to be.